PREDICTORS OF SOCIAL AND PSYCHOLOGICAL ADAPTATION OF THE UNEMPLOYED AND PEOPLE WITH REGULAR EMPLOYMENT - Rail M Shamionov (RUDN Journal of Psychology and Pedagogics, 2017)
The article discusses the results of a study on the socio-psychological adaptation predictors of the unemployed in relation to people with regular employment. It is assumed that adaptation of the employed and the unemployed is determined by various socio-psychological phenomena; definition of the phenomena will allow to develop programmes of adaptation for the unemployed with preservation of motivation for self-realization. In total, 362 people (33% of whom were male) took part in the study, including 196 unemployed. Standardized methods and scales developed by the authors for assessing the subject position characteristics and adaptive readiness of a person were used. It was found that the unemployed are characterized by lower indicators of socio-psychological adaptation and characteristics that are of paramount importance for adaptation - self-acceptance, acceptance of others, emotional comfort. Socio-demographic characteristics, scales of subjective position, adaptive readiness, subjective well-being and values were consistently introduced to the regression equation. It is shown that adaptive readiness and values are the strongest predictors for the employed, while indicators of subjective well-being and value are more significant for the unemployed. The general predictors of adaptation are the level of education, happiness (positively) and negative affect (negatively). In other cases, the predictors are strictly differentiated.